Building a theory by induction: The example of goal setting theory. (August 2020) - Locke, Edwin A.; Latham, Gary P.
This article discusses the development of goal setting theory through induction. The processes such as formulating concepts and definitions, measurement issues, data gathering, data integration and presentation, identifying moderators and mediators, resolving contradictions, noting issues in application, expansions and extensions, and the role of induction in deduction are explained. A multi-decade effort that involves these processes led to a useful theory that has withstood the test of time.